2010
DOI: 10.2353/ajpath.2010.090748
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Outgrowth Encompasses COL-I, FN1, and POSTN Up-Regulation and Assembly to Fibrillar Networks Regulating Cell Adhesion, Migration, and Growth

Abstract: Although the outgrowth of micrometastases into macrometastases is the rate-limiting step in metastatic progression and the main determinant of cancer fatality, the molecular mechanisms involved have been little studied. Here, we compared the gene expression profiles of melanoma lymph node micro- and macrometastases and unexpectedly found no common up-regulation of any single growth factor/cytokine, except for the cytokine-like SPP1. Importantly, metastatic outgrowth was found to be consistently associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
108
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 65 publications
10
108
1
1
Order By: Relevance
“…It has previously been suggested that a tumor may be perceived by the organism as a permanent wound, with tissue damage triggering a healing process that may in turn favor tumor growth and metastasis (23). The structural feature we described here in lung tumors - dense parallel fibers adjacent to tumor islets - has also been observed in human melanoma and breast cancer metastases (24). In a mouse breast tumor model, collagen strands adjacent to tumor nests adopt several patterns during carcinoma progression, including similar ring structures around tumor cell regions that were observed at early stages of tumorigenesis (25).…”
Section: Discussionsupporting
confidence: 54%
“…It has previously been suggested that a tumor may be perceived by the organism as a permanent wound, with tissue damage triggering a healing process that may in turn favor tumor growth and metastasis (23). The structural feature we described here in lung tumors - dense parallel fibers adjacent to tumor islets - has also been observed in human melanoma and breast cancer metastases (24). In a mouse breast tumor model, collagen strands adjacent to tumor nests adopt several patterns during carcinoma progression, including similar ring structures around tumor cell regions that were observed at early stages of tumorigenesis (25).…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, high levels of type 1 collagen have also been found in metastatic lesions (Brown et al, 1999;Jensen et al, 2002). Recently, Soikkeli and co-workers reported that both FN1 and Col1a1 are involved in promoting cell migration, invasion and metastasis due to their increased expression and interaction with other matrix network proteins (Soikkeli et al, 2010). However, similar to reports on the dual nature of CD44, there have also been reports of a decreased synthesis of collagen by cells in culture upon oncogenic transformation through treatment with viruses or chemical carcinogens (Adams et al, 1977;Smith and Niles, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…126 TNC, normally produced by fibroblasts, can also be expressed by BCSCs. 127 This aberrant expression of TNC by BCSCs exerts a metastasis-initiating effect for niche formation for lung colonization.…”
Section: Extracellular Matrix (Ecm) Proteinsmentioning
confidence: 99%